Tax Incentives and Business Performance: Impact on Sustainability of MSMEs in Surakarta City - Harimurti, Fadjar; Rispantyo, Rispantyo (International Journal of Economics (IJEC), 2024)
This research aims to analyze the influence of tax incentives on MSME performance and sustainability in the city of Surakarta. Data was collected through a survey of MSME players and analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The research results show that tax incentives have a positive and significant influence on MSME performance (path coefficient = 0.506, p < 0.001) and business sustainability (path coefficient = 0.253, p = 0.040). In addition, the performance of MSMEs contributes significantly to sustainability (path coefficient = 0.381, p = 0.002). These findings underscore the importance of supportive fiscal policies, such as tax incentives, to improve operational efficiency, strengthen liquidity, and facilitate sustainable investment. The implications of this research include the need for more specific fiscal policies to encourage sustainability, educating MSMEs about the benefits of sustainability, and further research on less accessible sectors, such as the creative economy and technological innovation.